Resilience Caregiver for Patients with Mental Disorders - Muh. Hamka; Ariyanti Saleh; Suni Hariati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This review aims to map and provide a general overview of the barriers and resilience strategies for Caregivers of patients with mental disorders who are hospitalized. This scoping review refers to Arksey and O'Malley's 2005 methodological framework which has been refined by JBI. The article search used five databases in the period 2012-2022, with the criteria: all studies with samples of Caregivers of patients with mental disorders who were hospitalized with English and Indonesian texts. As a result of the research, ten articles met the inclusion criteria. From the results of the review, it was found that there were three factors inhibiting the resilience of Caregivers of patients with mental disorders, namely personal, family and social factors. In conclusion, strategies to increase Caregiver resilience include personal, family, social background, social support and education factors. To overcome the factors inhibiting Caregiver resilience, namely by maximizing strategies for increasing the resilience of Caregivers for patients with mental disorders. Keywords: Caregiver, Mental Disorders, Resilience, Mental Hospital